2011
DOI: 10.1007/s13187-011-0219-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Written and Oral Measures of Comprehension of Cancer Information by English-as-a-Second-Language Chinese Immigrant Women

Abstract: The Short Test of Functional Health Literacy for Adults (S-TOFHLA) and Cloze test are commonly used tools to measure comprehension of health information (i.e., health literacy); however, little is known about their use in English-as-a-Second-Language (ESL) populations. In this study, we compared written (Cloze test) and oral (Teach Back) measures of colon cancer information comprehension among ESL Chinese immigrant women to Canada. Performances on colon cancer-specific measures were compared to a general measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Second, participants were given the option to complete the questionnaire in English or Portuguese; 86.1 % selected the Portuguese version, which potentially suggests lack of confidence in English comprehension. Previous studies have clearly shown that on average, immigrants are more confident in understanding medical information [ 29 , 30 ] and perform better on medical comprehension tests in their first language [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, participants were given the option to complete the questionnaire in English or Portuguese; 86.1 % selected the Portuguese version, which potentially suggests lack of confidence in English comprehension. Previous studies have clearly shown that on average, immigrants are more confident in understanding medical information [ 29 , 30 ] and perform better on medical comprehension tests in their first language [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the effects of health literacy on understanding show that low health literacy often leads to a poor understanding of information. McWhirter [35] found that S-TOFHLA scores correlated with Cloze scores but not with a teach-back method for their texts on colon cancer. Gazmararian et al [36] found that lower health literacy may play a role in prescription drug refill adherence.…”
Section: Factors Influencing Learning and Understandingmentioning
confidence: 99%
“…There is evidence that beliefs about the causes of cancer and its prevention may also vary from culture to culture. In Asian cultures, for example, cancer tends to be seen as a non-preventable and fatal illness (McWhirter et al 2011).…”
Section: Introductionmentioning
confidence: 99%